If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + 4(4x + -6) = 5 + -4(2x + 1) Reorder the terms: 8 + 4(-6 + 4x) = 5 + -4(2x + 1) 8 + (-6 * 4 + 4x * 4) = 5 + -4(2x + 1) 8 + (-24 + 16x) = 5 + -4(2x + 1) Combine like terms: 8 + -24 = -16 -16 + 16x = 5 + -4(2x + 1) Reorder the terms: -16 + 16x = 5 + -4(1 + 2x) -16 + 16x = 5 + (1 * -4 + 2x * -4) -16 + 16x = 5 + (-4 + -8x) Combine like terms: 5 + -4 = 1 -16 + 16x = 1 + -8x Solving -16 + 16x = 1 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. -16 + 16x + 8x = 1 + -8x + 8x Combine like terms: 16x + 8x = 24x -16 + 24x = 1 + -8x + 8x Combine like terms: -8x + 8x = 0 -16 + 24x = 1 + 0 -16 + 24x = 1 Add '16' to each side of the equation. -16 + 16 + 24x = 1 + 16 Combine like terms: -16 + 16 = 0 0 + 24x = 1 + 16 24x = 1 + 16 Combine like terms: 1 + 16 = 17 24x = 17 Divide each side by '24'. x = 0.7083333333 Simplifying x = 0.7083333333
| 5x^2-12x-65=0 | | 14*0.3= | | 2/3a^2b-1/6ab | | (2x-6)+(3x+4)=90 | | 4x^3+12x^2= | | y=(5x^2)-(2x)+3 | | 222+194+S=627 | | 32/2=×/1 | | 29+4y-2=15y-9-5y | | 13-2(x+51)=-19 | | 0.35(x+3)-.095(2x+28)= | | 222+194+5=627 | | (3x^2)-(5x)+1=0 | | 12x-7=0 | | 2X=4X/5/3 | | (x+8)-2(6x-4)= | | 2x-9y=14fory | | (5-12i)^1/2 | | 6x^2+4y^2-7x+y+2=0 | | -(x-6)-8(4+x)= | | 8x-4y-6y+5x+10= | | -4x+.66=2.3 | | x-5/2-6=x-4/3 | | m/15=9/32 | | -5x^2-14+x^4=0 | | 4x-5(5-x)= | | (-4y+4)-(-3y-8)=2 | | (8+2)(7+(2+4))=X | | V=LWHfrow | | 7-3(5-10)=67 | | (8+2)(7+(2+2))=X | | (5/11)(6) |